The use of high-resolution melting techniques for mutation screening of diseases caused by trinucleotide repeats expansion, with emphasis on the AR gene (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Trinucleotide repeat expansion (TRE) diseases are genetic diseases caused by an increase in the number of CAG, CGG, and CTG codons. CAG repeat expansion in exon 1 of the androgen receptor (AR) gene is known to be associated with disorders of sex development (DSD) and spinal and bulbar muscular atrophy (SBMA). Because the traditional Southern blot for CAG repeat expansion is laborious and time-consuming, this study was aimed to use high-resolution melting (HRM) analysis to screen the CAG repeat length of the AR gene in Indonesian patients with DSD. METHODS In total, 30 male patients with DSD (46, XY), one male patient with SBMA, and 30 healthy males (control) were included in the study. The CAG repeat length was determined using HRM analysis, and Sanger sequencing was used to confirm the CAG repeat length. RESULTS For the DSD cases and controls, the melting temperature (Tm) was within the normal range of 89-91.05°C; however, Tm was 92.65°C for the SBMA case. Sanger sequencing confirmed that DSD cases had 13-27 CAG repeats, and the SBMA case had 54 CAG repeats. CONCLUSIONS HRM analysis using polymerase chain reaction is a sensitive, effective, and rapid technique for screening CAG repeat expansion in exon 1 of the AR gene. This is the first technique for AR gene screening that may be applicable to other TRE diseases.